2018
DOI: 10.30442/ahr.0402-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of completion of Laboratory Request Forms in a tertiary health facility

Abstract: Background: Laboratory request form is an important means of interaction between clinicians and laboratory service providers. The omission of information on the request form may result in laboratory errors which may have a negative impact on patients’ outcome. Objective: To assess the pattern of completion of laboratory request forms in a tertiary facility. Methods: Two thousand, two hundred and forty-one laboratory request forms sent to the laboratory over a period of two months were assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
7
6
2
Order By: Relevance
“…There were only 1.0% (3/289) of the evaluated request forms with all the required information and the rest had one or more of the parameters missing. This result is similar to the finding by Oyedeji et al [9] and Oyelekan et al [10] [12] reported a similar finding. The time of collection of the specimen was indicated in 84.1% of the forms and this was higher than the findings reported in studies by Adekoge et al [13], Makubi et al [8], Oyelekan et al [10] and Olayemi & Asiamah-Broni [11] where the parameter was recorded in 10.3%, 1.5%, 0.7% and 0.0% of the request forms respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were only 1.0% (3/289) of the evaluated request forms with all the required information and the rest had one or more of the parameters missing. This result is similar to the finding by Oyedeji et al [9] and Oyelekan et al [10] [12] reported a similar finding. The time of collection of the specimen was indicated in 84.1% of the forms and this was higher than the findings reported in studies by Adekoge et al [13], Makubi et al [8], Oyelekan et al [10] and Olayemi & Asiamah-Broni [11] where the parameter was recorded in 10.3%, 1.5%, 0.7% and 0.0% of the request forms respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of clinical information, the diagnosis was filled in 85.8% of the request forms and this finding compares with the that by Nutt et al [16] of 80.9% but higher than the result by Makubi et al [8] of 37.9%. The clinical history was indicated in 14.9% of the forms and it is lower than the one reported by Makubi et al [8] Clinician's name and sign were available in 96.9% and 96.5% of the evaluated forms respectively and this finding is similar to that from studies by Oyelekan et al [10] and Jegede et al [12] where both the parameters were present in 93.8%…”
Section: Discussionsupporting
confidence: 69%
“…In this study, the overall fully completed request and report format is only 72.9% and 81.7% respectively. This is higher than comparing proportionally a study from Nigeria in which only 5 (0.2%) was fully completed [11]. However, lower than study from Addis Ababa, Ethiopia that 77.37 % of lab requests and 87.15% of laboratory report formats were fully completed [4].…”
Section: Discussionmentioning
confidence: 90%
“…The correct interpretation of the test results is a core point to patient management that highly based on the information given on the request and report form. Several studies have shown deficiencies in the filling of laboratory requests and report forms world widely [5,11,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation